Coffea arabica L. Resistant to Coffee Berry Borer (Hypothenemus hampei) Mediated by Expression of the Bacillus thuringiensis Cry10Aa Protein - Valencia-Lozano, Eliana; Cabrera-Ponce, Jose Luis; Noa-Carrazana, Juan C.; Ibarra, Jorge E. (Frontiers in Plant Science, 2021)
Coffea spp. are tropical plants used for brewed beverage from roasted and grounded seeds, the world´s favorite drink. It is the most important commercial crop-plant and the second most valuable international commodity after oil. Global coffee trade relies on two Coffea species: C. arabica L. (arabica coffee), comprising 60%, and C. canephora (robusta) comprising the remaining 40%. Arabica coffee has lower productivity and better market price than robusta. Arabica coffee is threatened by disease (i.e. coffee leaf rust), pests (i.e. Hypothenemus hampei or coffee berry borer (CBB) and nematodes) and susceptibility to climate change (i.e. drought, aluminum toxicity). Plant biotechnology by means of tissue culture inducing somatic embryogenesis (SE) process, genetic transformation and genome editing are tools that can help to solve, at least partially, these problems.